Психологічна мотивація споживача як основа ефективного брендингу - Оксенюк, Катерина Ігорівна (Хмельницький, 2025)
У статті розглядається важливість психологічної мотивації споживача як ключового елемента ефективного брендингу. Досліджено психологічні чинники, які впливають на поведінку споживача: потреби та бажання; мотивація; сприйняття; ставлення; спосіб життя; культурні чинники тощо. Особливу увагу при-ділено практичним аспектам застосування психологічних принципів у розробці маркетингових стратегій та комунікацій бренду. Проаналізовано, як розуміння мотивації може бути використане для формування сильного та впізнаваного бренду, підвищення лояльності споживача, збільшення обсягів продажів. Доведе-но, що глибоке розуміння психологічних потреб та бажань цільової аудиторії є визначальним фактором для створення релевантних комунікацій, формування лояльності та досягнення довгострокового успіху бренду на конкурентному ринку.

The article is devoted to a comprehensive study of the key role of psychological motivation of consumers as a fundamental basis for building effective and sustainable branding. The pupose of the study is a comprehensive analysis of how a deep understanding of the psychological factors influencing consumer behavior can be used to develop successful marketing strategies, build a strong brand image, increase consumer loyalty, and achieve long-term competitive advantages. The explores how consumers' deep psychological needs, desires, values, and emotional responses influence their brand perception, loyalty formation, and purchasing decisions. It reveals the relationship between consumers' internal motivations, needs, and desires and their response to a brand. Special attention is paid to the interaction between the consumer and the brand, determining what motives prompt consumers to choose a particular brand. The practical aspects of applying psychological principles to create effective branding strategies are examined in detail. It has been established that the key psychological factors that influence consumer behavior are: needs and desires; motivation; perception; learning; attitudes; lifestyle; cultural factors, ets. The importance of market segmentation based on consumer psychographic characteristics (values, lifestyle, personality) is emphasized for more precise targeting of marketing communications and creation of personalized offers that best match their individual motivations. The ethical aspects of using psychological knowledge in branding are considered, emphasizing the need for transparent and honest communication with consumers, as well as the avoidance of manipulative practices. It has been established that a deep understanding of the psychological needs and desires of the target audience is a determining factor for creating relevant communications, building loyalty, and achieving long-term brand success in a competitive market. Brands that are able to effectively use this knowledge to build emotionally meaningful relationships with their audience gain significant competitive advantages, ensure sustained consumer loyalty, and achieve achieve long-term growth
Consumer psychological motivation as the basis of effective branding
Keywords: брендинг; мотивація; психологічна мотивація; споживач; поведінка споживача; ефективність; потреби; емоції